INDIAN YAGYA-VARAHA IDOLS TRADITION: A SCULPTURAL AND PHILOSOPHICAL STUDY AND CONCEPTUAL PARALLELS WITH CONTEMPORARY ART - Soni, Gourav; Chauhan, Sadhana (International Journal of Research -GRANTHAALAYAH, 2026)
The present paper is dedicated to unique sculpture from the ancient Indian iconographic traditions, which strongly demonstrate the evolved practice of Indian iconography. Indian iconography has not been limited to the mere external beauty of deities, but has also been a tangible expression of philosophical, cosmic, and cultural thought. Among the ten incarnations of Vishnu, the third incarnation - the Varaha avatar is particularly significant because it is directly linked to the salvation of the earth and environmental balance. This paper presents a study of the unique and rare Yajna Varaha and other Varaha statues crafted within the Indian iconographic tradition. These statues are also known by names such as Pashu Varaha, Vishvarupa Varaha, and Sarvadevamaya Varaha. These statues depict Lord Vishnu in a fully boar form, with various deities etched throughout his body, making him not merely an incarnation of Vishnu but a symbol of all cosmic forces. This research analyzes the concept of the Varaha avatar, its iconographic features, and philosophical meanings, based on Vedic literature, scriptures, Puranas, Shilpa Shastra texts, and direct sculptural observation. A brief comparative study of complete Varaha statues preserved in the Central Museum (Indore), Eran District-Sagar (Madhya Pradesh), and the Gujari Mahal Museum (Gwalior) is an important aspect of this research. It also elucidates how the concept of the Varaha avatar is deeply connected to contemporary art issues such as environmental protection and the relationship between nature and humans. Conclusively, this research establishes that the Varaha statue is not only a classical religious symbol but also holds profound ideological relevance and relevance in contemporary art and environmental discourse. Keywords: Varaha avatar, Yagna varaha, Yajna Varaha Sculpture, Indian iconography, Vishnu Dashavatara, Sarvadevamay Varaha, Shilpa Shastra, Puranic tradition, cosmic symbolism, environmental consciousness, Indian classical art, iconography, Sculpture Studies, indian contemporary art.